Ekonomi Islam Sebagai Solusi Krisis Ekonomi - Hilman, Rifki Suja (FALAH Jurnal Ekonomi Syariah, 2017)
The economic crisis in perceptive Islam is inseparable from economic practices that are contrary to Islamic values, such as usury (monopoly), corruption, and other malpractices. But the common mistake made in identifying the root of the crisis that occurred only limited to the search on the symptom (symptoms). As a result, healing is only temporary, like analgesic drugs, temporarily relieving pain. At the Moments later, the crisis reappeared, even deeper and more serious. This paper tries to uncover some of the causes of the economic crisis, along with the solutions offered by Islamic economics as an effort to solve the crisis that has occurred.